Population Aging and Households’ Saving in the Russian Federation - Bussolo, Maurizio (World Bank, Washington, DC, 2015)
Using household data from the Russian Longitudinal Monitoring Survey, this paper assesses how aging affects saving. To overcome a systematic bias against the life-cycle hypothesis of survey data, the paper estimates how the age profile of saving changes when the micro data are corrected to account for the contribution to pensions (as additional saving) and receipt of benefits from pensions (as dissaving). With these corrections, the Russian data support the life-cycle hypothesis. A small decline in the aggregate saving rate, because of aging, can thus be expected. However, since aggregate saving rates result from a combination of age and cohort effects, this decline may not be significant. When extrapolating the rising trends of the cohort effect, the fact that younger generations are earning and saving more than older generation at the same age, the projection shows a growing aggregate saving rate. The changes in saving of future cohorts, for example because of changes in the growth rate of the economy, can affect the aggregate saving rate even more than aging.